# |
ODE |
Mathematica |
Maple |
\[
{}y^{3}+3 y^{\prime } y^{2} = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x = 3 x^{4}+y^{3}
\] |
✓ |
✓ |
|
\[
{}x \,{\mathrm e}^{y} y^{\prime } = 2 \,{\mathrm e}^{y}+2 x^{3} {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}2 x \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 4 x^{2}+\sin \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{y}+x \right ) y^{\prime } = -1+x \,{\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+\left (2 y+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x -y+\left (6 y-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+2 y^{2}+\left (4 x y+6 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{2}+3 x^{2}+\left (2 x^{2} y+4 y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+\frac {y}{x}+\left (y^{2}+\ln \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y \,{\mathrm e}^{x y}+\left (2 y+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )+\ln \left (y\right )+\left (\frac {x}{y}+{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +\arctan \left (y\right )+\frac {\left (x +y\right ) y^{\prime }}{1+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{3}+y^{4}+\left (3 y^{2} x^{3}+y^{4}+4 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )+\tan \left (y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )+x \sec \left (y\right )^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 x}{y}-\frac {3 y^{2}}{x^{4}}+\left (\frac {2 y}{x^{3}}-\frac {x^{2}}{y^{2}}+\frac {1}{\sqrt {y}}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}\frac {2 x^{{5}/{2}}-3 y^{{5}/{3}}}{2 x^{{5}/{2}} y^{{2}/{3}}}+\frac {\left (3 y^{{5}/{3}}-2 x^{{5}/{2}}\right ) y^{\prime }}{3 x^{{3}/{2}} y^{{5}/{3}}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+3 y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+3 y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+{\mathrm e}^{x}+\left (3 x^{2} y^{2}+\sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y+x^{4} y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}2 x y^{2}+x^{2} y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+x^{3} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 6 x^{2} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x y+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}6 x y^{3}+2 y^{4}+\left (9 x^{2} y^{2}+8 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{4}
\] |
✗ |
✗ |
|
\[
{}x^{3} y^{\prime } = x^{2} y-y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 3 x^{2} {\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-2 x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+y \,{\mathrm e}^{x y}+\left ({\mathrm e}^{y}+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y-x^{3} y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}3 x^{5} y^{2}+x^{3} y^{\prime } = 2 y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y = \frac {3}{x^{{3}/{2}}}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+\left (x -1\right ) y = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 6 y+12 x^{4} y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}+y \cos \left (x \right )+\left (x \,{\mathrm e}^{y}+\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{2} y^{2}+x^{{3}/{2}} y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 y+\left (1+x \right ) y^{\prime } = 3 x +3
\] |
✓ |
✓ |
|
\[
{}9 \sqrt {x}\, y^{{4}/{3}}-12 x^{{1}/{5}} y^{{3}/{2}}+\left (8 x^{{3}/{2}} y^{{1}/{3}}-15 x^{{6}/{5}} \sqrt {y}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}3 y+y^{4} x^{3}+3 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 2 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right ) y^{\prime }+y = \left (2 x +1\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \left (y+7\right ) x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \left (y+7\right ) x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y^{3}-x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-3 x^{2}-2 y^{2}}{4 x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 y+x}{-3 x +y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y+2 x}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cot \left (x \right ) \left (\sqrt {y}-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}3 y+y^{\prime } = {\mathrm e}^{-2 t}+t
\] |
✓ |
✓ |
|
\[
{}-2 y+y^{\prime } = {\mathrm e}^{2 t} t^{2}
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = 1+t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}\frac {y}{t}+y^{\prime } = 3 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}-2 y+y^{\prime } = 3 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}2 y+t y^{\prime } = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}2 t y+y^{\prime } = 2 t \,{\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}4 t y+\left (t^{2}+1\right ) y^{\prime } = \frac {1}{\left (t^{2}+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y+2 y^{\prime } = 3 t
\] |
✓ |
✓ |
|
\[
{}-y+t y^{\prime } = t^{2} {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = 5 \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y+2 y^{\prime } = 3 t^{2}
\] |
✓ |
✓ |
|
\[
{}-y+y^{\prime } = 2 t \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}2 y+y^{\prime } = t \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}2 y+t y^{\prime } = t^{2}-t +1
\] |
✓ |
✓ |
|
\[
{}\frac {2 y}{t}+y^{\prime } = \frac {\cos \left (t \right )}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}-2 y+y^{\prime } = {\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}2 y+t y^{\prime } = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}4 t^{2} y+t^{3} y^{\prime } = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}\left (t +1\right ) y+t y^{\prime } = t
\] |
✓ |
✓ |
|
\[
{}-\frac {y}{2}+y^{\prime } = 2 \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}-y+2 y^{\prime } = {\mathrm e}^{\frac {t}{3}}
\] |
✓ |
✓ |
|
\[
{}-2 y+3 y^{\prime } = {\mathrm e}^{-\frac {\pi t}{2}}
\] |
✓ |
✓ |
|
\[
{}\left (t +1\right ) y+t y^{\prime } = 2 t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}2 y+t y^{\prime } = \frac {\sin \left (t \right )}{t}
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right ) y+\sin \left (t \right ) y^{\prime } = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}\frac {y}{2}+y^{\prime } = 2 \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}\frac {2 y}{3}+y^{\prime } = 1-\frac {t}{2}
\] |
✓ |
✓ |
|
\[
{}\frac {y}{4}+y^{\prime } = 3+2 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}-y+y^{\prime } = 1+3 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}-\frac {3 y}{2}+y^{\prime } = 2 \,{\mathrm e}^{t}+3 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{\left (x^{3}+1\right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{2} \sin \left (x \right )+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{2}-1}{3+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )^{2} \cos \left (2 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-{\mathrm e}^{-x}+x}{{\mathrm e}^{y}+x}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \frac {x^{2}}{1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1-2 x \right ) y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1-2 x}{y}
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } {\mathrm e}^{-x} = 0
\] |
✓ |
✓ |
|
\[
{}r^{\prime } = \frac {r^{2}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x}{y+x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y^{2}}{\sqrt {x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x}{1+2 y}
\] |
✓ |
✓ |
|